Ocular Surface Disorders in a Group of Egyptian Children with End Stage Renal Failure on Dialysis: A Cross-Sectional Study - Mohamed Anbar; Ahmed R. H. Ahmed; Abdel-Azeem M. El-Mazary; Ramadan A. Mahmoud (Journal of Ophthalmology)
Purpose. To investigate tear function, ocular manifestations, and squamous metaplasia of the conjunctival epithelium (SMCE) in children with end stage renal failure (ESRF) on dialysis. Methods. Thirty children with ESRF and 20 age and sex matched controls during the period from January 2014 to May 2015 underwent full ophthalmologic examination and the tear function was investigated by the Schirmer and tear film break-up time (TBUT) tests. SMCE was evaluated by impression cytology and immunocytochemistry. The correlations of tear function status with ESRF-related clinical and biochemical variables were measured statistically. Results. Dry eye symptoms were detected in 26% of children with ESRF, compared with none of the controls (P=0.05) and SMCE was almost absent. Values of the Schirmer and TBUT tests were significantly lower in children with ESRF for right eye (t=24.63, P=0.01, and t=11.9, P=0.002, resp.) and left eye (t=24.7, P=0.02, and t=11.4, P=0.0004, resp.). TBUT and the Schirmer test values were correlated inversely with the duration of ESRF (R=-0.45, P=0.01, and R=-0.46, P=0.01, resp.) and with the duration of dialysis (R=-0.39, P=0.03, and R=-0.45, P=0.01, resp.). None of the following parameters was associated with distorted tear function including serum creatinine, electrolytes, parathyroid hormone, total protein, albumin, CBC parameters, and systolic or diastolic blood pressure. Conclusion. The basal tear secretion and tear film stability were lower while the dry eye symptoms such as itching and redness were more common among children with ESRF. The duration of ESRF and dialysis duration seem to be related to the disturbances in tear secretion and tear film stability. However, SMCE is very rare.